Dynamics of dust particles in a plasma jet - Kravchenko, O.Yu.; Maruschak, I.S. (Вопросы атомной науки и техники, 2017)
In this paper carry out the computer simulation of the plasma jet with dust particles, which expands in rarefied neutral gas. The problem is considered in the framework of multi-fluid hydrodynamic model, which takes into account the difference in velocity and temperature of the plasma component. Calculations performed using method “big particles” for different ionization degree of plasma, its density and radii of dust particles. The spatial distributions of plasma parameters and dust components obtained at different time points after injection plasma jet. It is shown that at the large ionization degree of plasma (α> 0.001) velocity of the dust particles significantly decreased compared to the case of weakly ionized plasma stream. This result can be explained by deceleration of dust particles by an electric field, the effect of which increases with increasing concentrations of electrons and ions.